Risk of Ischemic Stroke Associated with the Use of Antipsychotic Drugs in Elderly Patients: A Retrospective Cohort Study in Korea - Shin, Ju-Young (PLoS One, 2015)
OBJECTIVE: Strong concerns have been raised about whether the risk of ischemic stroke differs between conventional antipsychotics (CAPs) and atypical antipsychotics (AAPs). This study compared the risk of ischemic stroke in elderly patients taking CAPs and AAPs. METHOD: We conducted a retrospective cohort study of 71,584 elderly patients who were newly prescribed the CAPs (haloperidol or chlorpromazine) and those prescribed the AAPs (risperidone, quetiapine, or olanzapine). We used the National Claims Database from the Health Insurance Review and Assessment Service (HIRA) from January 1, 2006 to December 31, 2009. Incident cases for ischemic stroke (ICD-10, I63) were identified. The hazard ratios (HR) for AAPs, CAPs, and for each antipsychotic were calculated using multivariable Cox regression models, with risperidone as a reference. RESULTS: Among a total of 71,584 patients, 24,668 patients were on risperidone, 15,860 patients on quetiapine, 3,888 patients on olanzapine, 19,564 patients on haloperidol, and 7,604 patients on chlorpromazine. A substantially higher risk was observed with chlorpromazine (HR = 3.47, 95% CI, 1.97–5.38), which was followed by haloperidol (HR = 2.43, 95% CI, 1.18–3.14), quetiapine (HR = 1.23, 95% CI, 0.78–2.12), and olanzapine (HR = 1.12, 95% CI, 0.59–2.75). Patients who were prescribed chlorpromazine for longer than 150 days showed a higher risk (HR = 3.60, 95% CI, 1.83–6.02) than those who took it for a shorter period of time. CONCLUSIONS: A much greater risk of ischemic stroke was observed in patients who used chlorpromazine and haloperidol compared to risperidone. The evidence suggested that there is a strong need to exercise caution while prescribing these agents to the elderly in light of severe adverse events with atypical antipsychotics.